C-shaped root canal configuration in mandibular second premolar: Report of an unusual case and its endodontic management - Dipali Y Shah (Wolters Kluwer Medknow Publications, 2012)
The C-shaped root canal system is an aberration of the root canal system in which a characteristic fin or web connects individual canals, resulting in a C-shaped cross section. This configuration has been rarely reported in the mandibular second premolar. The only other known reported case of a C-shaped canal, with its configuration, in relation to mandibular second premolar is of an extracted tooth. The purpose of this report is to describe the diagnosis, configuration and endodontic management of C-shaped root canal in mandibular second premolar. Clinical techniques to addresses the challenges in endodontic disinfection as well as cleaning and shaping of the C-shaped canal, which is prone to endodontic mishaps, are also discussed in this case report. Reporting of this case emphasizes the need and added advantage of using the dental operating microscope hand in hand with conventional radiography in management of the C-shaped root canal configuration.